Nutrition, sports, and Covid-19 lockdown impact on young competitive artistic swimming athletes - Russo, M. T.; Fadda, J.; Angioni, A. (Austin Journal of Nutrition & Metabolism, 2020)
Young artistic swimmers must face to a unique aquatic sport which requires a variety of athletic abilities, such as endurance, power, agility, acrobatics, and flexibility, together with a sense of rhythm and team spirit. This activity involves both aerobic and anaerobic metabolism, which requires high energy expenditure. Therefore, correct nutritional intake should be available. However, nutritional needs for growth and training are in contrast with the contemporary attempt to achieve unrealistic body shape goals. The energy requirements of artistic swimmers are challenging and cannot be able to sustain healthy body function, causing a higher risk of developing disordered eating/eating disorders in young female athletes, or eating anxiety, fearing that eating appropriate foods and beverages negatively alter body composition and increase body mass. Moreover, female athletes can face some additional dietary challenges, including additional requirements such as iron and calcium. COVID-19 lockdown has highlighted a worrying discrepancy among macronutrients intake during the training period and the suggested ratio of macronutrients for healthy nutrition, with an inverted ratio fat/protein, and lower energy intake in respect to the consumed. Young artistic swimming athletes showed the absence of nutritional knowledge and the composition of the food. Moreover, families and coaches are not prepared to assist athletes in the problematic choice of foods that are important for growth and sports performance. Therefore, nutrition is committed to external inputs and social suggestions. Adequate guidelines should be made available for athletes, families, and the technical environment to support food choices and possible alternatives. aspects affecting their nutritional needs [4]. Nutritional needs are also related to Body Composition (BC) related to sports performance. Therefore, the BC for the same athlete changes during the year within its training season (preseason, transition period, competitive period, and sometimes an injury period) [5]. Adult competitive athletes can control the BC, by BMI (Body Mass Index), DEXA (Dual-Energy X-ray Absorptiometry), BIA (bioelectrical, impedance analysis), and anthropometry. A different contest is found for young athletes where only seldom studies on BC are carried out, restricted to not adequate to the training performance or evident physical problems. The requested certificate of competitive activity does not give any information relating BC and nutritional needs of the athlete. Whatever the sport, it is essential for an athlete's body to works at maximum efficiency and food choices meeting nutritional needs are an integral part of an athlete's regime. Essential differences in the nutritional needs in the different sports include the best foods, timing of food and liquid intake to achieve maximum energy production. Therefore, until an athlete does not understand the relationship